Synthesis and activity evaluation of heterometallic nano oxides integrated ZSM-5 catalysts for palm oil cracking to produce biogasoline - Ahmad, M.; Farhana, R.; Abdul Raman, Abdul Aziz; Bhargava, S.K. (Elsevier, 2016)
Biofuels produced from palm oil have shown great potential as a useful fossil fuel substitute and are environmental friendly. Utilization of palm oil as biofuel requires zeolite based catalytic technology that facilitates selective conversion of substrates to desired products, including biogasoline and biodiesel. However, the synthesis and integration of suitable zeolite based supported catalysts for the desired products are the key challenges in biofuel production. The alternative to overcome these problems is to use nano heterometallic materials supported on zeolite catalysts. In this study, Zeolite Socony Mobile-5 (ZSM-5) based catalysts loaded with heterometallic nano oxides were synthesized. Next, the catalysts used for the palm oil cracking to produce biogasoline were characterized by field emission electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX), high resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR) and Brunauer, Emmett and Teller (BET) analysis. Taguchi method was used to assess and optimize the catalytic cracking process. The catalytic cracking results illustrated that under optimized conditions, ZSM-5 (30), Fe-Zn-Cu-ZSM-5 (31), Fe-Zn-Cu-ZSM-5 (32) and Fe-Zn-ZSM-5 (33) yielded 14%, 59%, 49% and 56% biogasoline, respectively. Higher efficiency of Fe-Zn-Cu-ZSM-5 (31) might be attributed to higher content of loaded metal oxides as compared to the other synthesized catalysts. The yield of biogasoline in this study, catalyzed by Fe-Zn-Cu-ZSM-5 (31), was 8% more than the literature values. Therefore, the present study proved that the newly developed Fe-Zn-Cu-ZSM-5 (31) was an efficient and economical catalyst for producing biogasoline from cracking of palm oil.